Determinan Pembiayaan UMKM di Indonesia Tahun 2011-2015: Pendekatan Generalized Method Of Moment (GMM) - Sagitaria Saputri; Muhammad Ghafur Wibowo (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2018)
Abstrak Penelitian ini mengidentifikasikan mengenai faktor pembiayaan yang menjadi isu penting pertumbuhan UMKM. Pembiayaan yang disalurkan setiap provinsi belum merata dan masih adanya gap. Sedangkan permodalan UMKM begitu penting dalam mengatasi kemiskinan, mengurangi pengangguran serta meningkatkan pertumbuhan ekonomi. Metode yang digunakan dalam penelitian ini adalah analisis generalized method of moment (GMM) Arellano Bond dengan periode penelitian dari Januari 2011 hingga Juni 2015. Dari hasil analisis GMM Arellano Bond dapat disimpulkan bahwa variabel internal perbankan syariah DPK dan NPF memiliki pengaruh negatif signifikan terhadap pembiayaan UMKM. Sedangkan FDR memberi dampak positif signifikan terhadap pembiayaan UMKM. Kemudian variabel makroekonomi berupa IPI memberikan dampak positif signifikan terhadap pembiayaan UMKM. Penelitian ini merekomendasikan pentingnya peningkatan proporsi pembiayaan UMKM dengan mengoptimalkan dana pihak ketiga untuk ditempatkan pada sektor riil. Kata Kunci: Usaha Mikro Kecil dan Menengah (UMKM), perbankan syariah, GMM Arellano-Bond Abstract This research identifies the financing factor that is still an important issue of SMEs survival. The financing distributed by each province is not evenly distributed and there is existing gap. While the capital of SMEs is so important in overcome poverty and unemploymentas well as in increasing theeconomic growth. The  purpose of this research is to know the impact of internal variables of Islamic banking in the form of Third Party Fund (DPK), Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF) and external variable of Islamic banking from Industrial Production Index (IPI) to SMEs financing. The method reference is Arellano Bond's generalized method of moment (GMM) analysis with the research period from January 2011 to June 2015. The objects of the research are five provinces with the largest SMEs financing in Indonesia. From the analysis of GMM Arellano Bond, it can be concluded those internal variables of Islamic bankingare NPF and DPK have a negative significant impact on SMEs financing. While the FDR gives a positive significant impact on the SMEs financing. Then macroeconomic variable in the form of IPI give positive significant impact to SMEs financing. This study recommends the importance of increasing the proportion of SMEs financing by optimizing third party funds to be placed on the real sector. Keywords:Small and Medium entreprises (SMEs), islamic banking, GMM Arellano Bond